Back to the Future of qEEG: Lifespan Normative Modeling of Spectral Ratios and Functional Indices with Potential Applications to Therapeutic Monitoring - J. Bosch-Bayard; J. Guerrero-Sauzameda; R. I. Bosch-Bayard; R. Pérez-Elvira; A. Bosch-Castro; J. Sánchez-Rodríguez; A. Flores; K. Flores; E Resendiz-Flores; A. Ferrando; P. Ferrando; L. Galán-García; et al. (Brain Topography, 2026)
Quantitative EEG (qEEG) provides objective, millisecond-resolution measures of brain dynamics. Despite decades of methodological advances, clinically relevant derived indices—spectral power ratios, cognitive-emotional state markers, and physiological parameters—are typically reported as raw values without the normative context required for individualized clinical inference. To develop the first systematic age-dependent normative models for this family of derived qEEG indices using a multinational database, enabling probabilistic Z-score interpretation at the individual level with potential applications in objective therapeutic monitoring. Normative modeling was applied to the HarMNqEEG database ( n = 1,564 neurologically healthy participants, ages 5–97, 9 countries, eyes-closed resting state). Electrode-level Spectral Normalization (ESN) removed inter-individual and inter-device amplitude variability while preserving the neurophysiological interpretability of each index. Age-dependent normative trajectories were estimated using Generalized Additive Models for Location, Scale, and Shape (GAMLSS) with P-splines on log(age), allowing conditional mean and variance to vary non-linearly across the lifespan. GAMLSS modeling revealed significant non-linear age-dependent trajectories for all indices. Slow-wave-dominated ratios showed steep decreases from childhood to early adulthood, consistent with cortical maturation; alpha-dominated indices increased during adolescence before stabilizing. ESN normalization yielded well-calibrated normative residuals across the full age range for all indices, except Valence. For the Valence index, a quantile regression model is provided as the recommended normative reference due to its spike-and-slab marginal distribution. These normative models provide a principled, age-adjusted probabilistic framework for individual-level qEEG interpretation, based on eyes closed resting state recordings, laying the methodological groundwork for future clinical validation in diagnostic and therapeutic monitoring applications. The ESN strategy requires no knowledge of recording equipment, ensuring broad applicability across clinical and research settings.

Optimization of protein requirements and feed restriction in Penaeus vannamei (Boone, 1931) biofloc culture - S. Ferrando-Juan; J. Gómez-Aguilera; S. Martínez-Llorens; A. Tomás-Vidal; M. Rodilla; M. Jover-Cerdá; F. J. Moyano; D. S. Peñaranda (Aquaculture International, 2026)

Maximum Individual Wave Height Prediction Using Different Machine Learning Techniques with Data Collected from a Buoy Located in Bilbao (Bay of Biscay) - Lucia Porlan-Ferrando; J. David Nuñez-Gonzalez; Alain Ulazia Manterola; Nahia Martinez-Iturricastillo; John V. Ringwood (Journal of Marine Science and Engineering, 2025)
Accurate prediction of extreme waves, particularly the maximum wave height and the ratio between the maximum and significant wave heights of individual waves, is crucial for maritime safety and the resilience of offshore infrastructure. This study employs machine learning (ML) techniques such as linear regression modeling (LM), support vector regression (SVR), long short-term memory (LSTM), and gated recurrent units (GRU) to develop predictive models based on historical data (1990–2024) obtained from a buoy at a specific oceanic location. The results show that the SVR model provides the highest accuracy in predicting the maximum wave height (Hmax), achieving a coefficient of determination (R2) of 0.9006 and mean squared error (MSE) of 0.0185. For estimation of the ratio between maximum and significant wave heights (Hmax/Hs), the SVR and LM models exhibit comparable performance, with MSE values of 0.0229. These findings have significant implications for improving early warning systems, optimizing the structural design of offshore infrastructure, and enhancing the efficiency of energy extraction under changing climate conditions.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Lipid distribution and composition in Antarctic toothfish before and after reproductive migration: implications for the life cycle - Davide Di Blasi; Stefano Aicardi; Giorgia Allaria; Erica Carlig; Sara Ferrando; Laura Ghigliotti; Elena Grasselli; Annalisa Salis; Marino Vacchi; Steven J. Parker (Polar Biology, 2024)

Update on the status of the contamination by organotin compounds in sediment of Nuevo Gulf, Argentina. Insights from field and experimental studies - N.A. Gomez; J. Sturla Lompré; A. Ferrando; M. Garrido; C.E. Domini (Marine Pollution Bulletin, 2024)

Fields with no recent legume cultivation have sufficient nitrogen-fixing rhizobia for crops of faba bean (Vicia faba L.) - Marta Maluk; Francesc Ferrando-Molina; Laura Lopez del Egido; Adrian Langarica-Fuentes; Genet Gebre Yohannes; Mark W. Young; Peter Martin; Richard Gantlett; Greg Kenicer; Cathy Hawes; Graham S. Begg; Richard S. Quilliam; et al. (Plant and Soil, 2022)
Purpose (1) To assess the biological N fixation (BNF) potential of varieties of faba bean ( Vicia faba L.) cropped with or without compost in an experimental field-scale rotation with no recent history of legumes, (2) to enumerate soil populations of Rhizobium leguminosarum sv. viciae ( Rlv ), and to genetically characterize the nodulating Rlv strains, (3) compare BNF with other sites in Britain. Methods BNF was evaluated from 2012 to 2015 using 15 N natural abundance. Treatments were either PK fertilizer or compost. Soil rhizobial populations were determined using qPCR, the symbiotic rhizobia genotyped (16 S rRNA, nodA and nodD genes), and their BNF capacity assessed ex situ . The reliance of legumes on BNF at other British sites was estimated in a single season, and their nodulating symbionts examined. Results Faba bean obtained most of its N through BNF (>80%) regardless of variety or year. N-accumulation by cvs Babylon and Boxer increased with compost treatment in 2014/2015. Rhizobial populations were c. 10 5 -10 6 Rlv cells g −1 soil regardless of field or treatment. 157 Rlv microsymbionts grouped into two large nodAD clades; one mainly from V. faba , and the other from various legumes. All isolates nodulated, and some performed better than commercial inoculant strains. Conclusions Faba bean can provide most of its nitrogen through BNF and leave economically valuable residual N for subsequent crops. Recent legume cropping in northern Europe is not essential for effective nodulation: rhizobia may persist in a range of farmland locations. Nevertheless, there is the potential to apply elite rhizobial strains as inoculants in some soils.

Metabolic effects of high-intensity interval training and essential amino acids - Katie R. Hirsch; Casey E. Greenwalt; Hannah E. Cabre; Lacey M. Gould; Gabrielle J. Brewer; Malia N. M. Blue; Arny A. Ferrando; Kim M. Huffman; Elizabeth J. Mayer-Davis; Eric D. Ryan; Abbie E. Smith-Ryan (European Journal of Applied Physiology, 2021)

Olfaction in the Antarctic toothfish Dissostichus mawsoni: clues from the morphology and histology of the olfactory rosette and bulb - Sara Ferrando; Andrea Amaroli; Lorenzo Gallus; Davide Di Blasi; Erica Carlig; Marino Rottigni; Marino Vacchi; Steven J Parker; Laura Ghigliotti (Polar Biology, 2019)

Surface egg structure and early embryonic development of the Antarctic toothfish, Dissostichus mawsoni Norman 1937 - Laura Ghigliotti; Sara Ferrando; Davide Di Blasi; Erica Carlig; Lorenzo Gallus; Darren Stevens; Marino Vacchi; Steven J Parker (Polar Biology, 2018)

Determination of probabilities for the generation of high-discharge flows in the middle basin of Elqui River, Chile - Iván P. Vergara Dal Pont; Fernanda A. Santibañez Ossa; Diego Araneo; Francisco J. Ferrando Acuña; Stella M. Moreiras (Natural Hazards, 2018)

Why blue tongue? A potential UV-based deimatic display in a lizard - Arnaud Badiane; Pau Carazo; Samantha J. Price-Rees; Manuel Ferrando-Bernal; Martin J. Whiting (Behavioral Ecology and Sociobiology, 2018)

Gross morphology and histology of the olfactory organ of the Greenland shark Somniosus microcephalus - S. Ferrando; L. Gallus; L. Ghigliotti; M. Vacchi; J. Nielsen; J. S. Christiansen; E. Pisano (Polar Biology, 2016)

The training-induced changes on automatism, conduction and myocardial refractoriness are not mediated by parasympathetic postganglionic neurons activity - M. Zarzoso; L. Such-Miquel; G. Parra; L. Brines-Ferrando; L. Such; F. J. Chorro; J. Guerrero; A. Guill; J. E. O’Connor; A. Alberola (European Journal of Applied Physiology, 2012)

Heme oxygenase 1 (HO-1) challenges the angiogenic switch in prostate cancer - M. Ferrando; G. Gueron; B. Elguero; J. Giudice; A. Salles; F. Coluccio Leskow; E. A. Jares-Erijman; L. Colombo; R. Meiss; N. Navone; A. De Siervi; E. Vazquez (Angiogenesis, 2011)

Polymorphism of the Goat Agouti Signaling Protein Gene and Its Relationship with Coat Color in Italian and Spanish Breeds - B. Badaoui; M. D’Andrea; F. Pilla; J. Capote; A. Zidi; J. Jordana; A. Ferrando; J. V. Delgado; A. Martínez; O. Vidal; M. Amills (Biochemical Genetics, 2011)

Population genetic structure and distribution of introduced American mink (Mustela vison) in Spain, based on microsatellite variation - Roberta Lecis; A. Ferrando; J. Ruiz-Olmo; S. Mañas; X. Domingo-Roura (Conservation Genetics, 2008)

Effect of an Acaricide on the Reproduction and Survival of Daphnia magna - M. J. Villarroel; E. Sancho; M. D. Ferrando; E. Andreu-Moliner (Bulletin of Environmental Contamination and Toxicology, 1999)